The From and Symbolic Meaning of the Costume in Geleng Ro'om Dance by Dimas Pramuka Admaji - Hira riksani abtazarin Abtazarin; Enie Wahyuning (Universitas Negeri Surabaya, 2025)
Geleng Room Dance is a creative dance choreographed by Dimas pramuka Admaji, inspired by the character of Madurese women. This character is espressed through distinctive movements, properties, and costumes. The costumes in Geleng Room Dance not only serves as a performance complement but also carries symbolic meanings that represent the cultural identity of the madurese community. Therefore, this study aims to describe the from of the costume and analyze it’s symbolic meanings in Geleng Room Dance by Dimas Pramuka Admaji. This study employed a qualitative approach using descriptive qualitative research. The data were collected through observation, in-depth interviews with the choreographer and relevant informants, and documentation studies. Data validity was ensured through source triangulation and technique triangulation. The data were analyzed using the stages of data reduction, data display, and conclusion drawing. The findings reveal that the costume of Geleng Ro'om Dance consists of several main elements, including a kebaya, cloth or sarong, shawl, and various supporting accessories such as a hair bun, head ornaments, necklaces, bracelets, and earrings. The forms, colors, motifs, and accessories are influenced by the cultural characteristics of Madura. Based on Stuart Hall's theory of representation, the costume symbolically represents beauty, elegance, assertiveness, courage, and the strong character of Madurese women. Therefore, the costume in Geleng Ro'om Dance functions not only as an aesthetic element of the performance but also as a medium for representing the cultural values embodied in the dance